Amiloride‐sensitive fluid resorption in NCI‐H441 lung epithelia depends on an apical Cl− conductance. Issue 1 (16th January 2014) - Korbmacher, Jonas P.; Michel, Christiane; Neubauer, Daniel; Thompson, Kristin; Mizaikoff, Boris; Frick, Manfred; Dietl, Paul; Wittekindt, Oliver H.
Abstract Proper apical airway surface hydration is essential to maintain lung function. This hydration depends on well‐balanced water resorption and secretion. The mechanisms involved in resorption are still a matter of debate, especially as the measurement of transepithelial water transport remains challenging. In this study, we combined classical short circuit current (ISC) measurements with a novel D2O dilution method to correlate ion and water transport in order to reveal basic transport mechanisms in lung epithelia. D2O dilution method enabled precise analysis of water resorption with an unprecedented resolution. NCI‐H441 cells cultured at an air–liquid interface resorbed water at a rate of 1.5 ± 0.4 μL/(h cm2). Water resorption and ISC were reduced by almost 80% in the presence of the bulk Cl− channel inhibitor 5‐nitro‐2‐(3‐phenylpropylamino)benzoic acid (NPPB) or amiloride, a specific inhibitor of epithelial sodium channel (ENaC). However, water resorption and ISC were only moderately affected by forskolin or cystic fibrosis transmembrane regulator (CFTR) channel inhibitors (CFTRinh‐172 and glybenclamide). In line with previous studies, we demonstrate that water resorption depends on ENaC, and CFTR channels have only a minor but probably modulating effect on water resorption. However, the major ENaC‐mediated water resorption depends on an apical non‐CFTR Cl− conductance.